Mоdern Ukrainian theater in the context of national archetypes formation - Zinchenko, Daria (Ukrainian Cultural Studies, 2025)
Background. In the process of forming national cultures, universal archetypes, reflected in literary and theatrical images, play a crucial role as carriers of national identity. Literature and theater, as forms of socio-cultural communication, not only represent these archetypes but also actively influence the processes of collective self-identification. The purpose of the study is to identify the modern theatrical transformation of nation-building archetypes, established in Ukrainian literary tradition.Methods. Methodology is based on historical, cultural, and semiotic approaches, which enable the study of theater as a tool for forming national archetypes.Results. Ivan Kotliarevsky's work, especially his Aeneid, served as a starting point for the formation of Ukrainian national consciousness in literature, akin to how the Renaissance and Classicism fostered the development of national cultures in European countries through reinterpretation of ancient traditions. By combining folk comic culture with the European classical heritage, Kotliarevsky created a new Ukrainian hero – the Cossack – as a national archetype symbolizing strength, will, and connection to historical memory. His works became a cultural milestone, initiating modern artistic thought. In his play Natalka Poltavka, he also laid the groundwork for female archetypes, portraying images of dignity, resilience, and fidelity. Developing these ideas, Taras Shevchenko introduced new archetypes – the Cossack-defender and the wise maiden – imbuing them with socio-political and moral dimensions. His oeuvre became a cornerstone in constructing a new Ukrainian identity. In the second half of the 19th century, the theater of the "Coryphaei", through the efforts of Kropyvnytskyi, Sadovskyi, and Saksahanskyi, ensured the professionalization of the stage and the adaptation of these archetypes to the theatrical space. The modernization of Ukrainian theater, particularly through new scenographic solutions and psychological depth in acting, reinforced its role as a center of national self-awareness and cultural continuity.Conclusions. Modern Ukrainian theater, grounded in the archetypes established in the works of Kotliarevsky and Shevchenko, has evolved into an essential instrument of national self-identification. Its aesthetic and ideological evolution from ethnographism to modernism has contributed to the professionalization of the art and deepened the national cultural discourse.
Keywords: Archetypes, Ukrainian classical literature, theatre, modern culture, nation